Comparative transcriptome analysis of the differentiating gonads in Scatophagus argus - Mustapha, Umar Farouk; Peng, You-Xing; Huang, Yuan-Qing; Assan, Daniel; Zhi, Fei; Shi, Gang; Huang, Yang; Li, Guang-Li; Jiang, Dong-Neng (Frontiers in Marine Science, 2022)
The reproductive-related studies, including genetic and genomic such as gonadal transcriptome analyses, have previously focused on the adult spotted scat, with little information on juvenile fish. Transcriptomics is a powerful tool that allows for massive parallel analysis to identify differential expression and the patterns of gene expression holistically at a particular stage in a cell or tissue development. This study presents the first report on gonadal transcriptome analysis of the differentiating (juvenile; 4 months after hatch; stage I ovary and testis) spotted scat gonads. The study revealed potential reproduction and gonadal development-related genes. A total of 25936 genes were identified, of which 16248 were co-expressed, 17893 and 17258 expressed in males and females, respectively, from sequence data of testis I (n = 3) and ovary I (n = 2). A total of 6549 differentially expressed genes (DEGs) were identified between males and females. Genes attributable to male gonad development pathway such as dmrt1, gsdf, and amh are significantly expressed in differentiating testes, while female-related genes such as foxl2, cyp19a1a, 42sp50 and sox3 were expressed considerably in differentiating ovaries. In addition, dmrt1/dmrt1y was not expressed in the female (FPKM=0.00), while its paralog dmrt1b was expressed in both males and females. In the male pathway, dmrt1y and gsdf are critical for sex determination and maintenance while foxl2/foxl3 and cyp19a1a are critical in the female development pathway. The current studies provide an insight into the expression patterns of sex and gonadal-related genes in differentiating gonads of spotted scat.